IMPLEMENTATION OF CHARACTER EDUCATION IN HIGHER EDUCATION: STRATEGIES, CHALLENGES, AND IMPACT - Attruk, Muhammad Fariq Heemal; A'yun, Qurrotul; Mujahidah, Nisak UI (EDUCATUM: Scientific Journal of Education, 2024)
The implementation of character education in higher education plays a pivotal role in shaping students with both academic excellence and moral integrity. This literature review explores strategies, challenges, and the impacts of character education across Indonesian universities. Strategies employed include integrating character values into curricula, leveraging religion-based education, utilizing technology, and aligning educational programs with local wisdom. Examples include the use of the AIKA curriculum at Universitas Muhammadiyah Prof. Dr. Hamka and religion-based activities at Universitas Islam Negeri Sumatera Utara, which aim to foster traits such as honesty, discipline, and empathy. Additionally, institutions like Universitas Negeri Surabaya have adopted digital-based approaches to instill values relevant to the modern era. Despite these advances, numerous challenges persist. Limited resources, cultural diversity, and inadequate evaluation frameworks hinder the optimal implementation of character education. For instance, the lack of comprehensive assessments of students’ attitudes and behaviors limits the visible impact on character formation. The COVID-19 pandemic further highlighted these challenges by disrupting traditional interaction-based teaching methods, demanding rapid adjustments to online platforms. This study highlights the significant role of local wisdom and religious values in fostering ethical behavior, responsibility, and social care among students. However, it also emphasizes the need for stronger policy support, resource allocation, and innovative approaches to overcome existing challenges. By addressing these gaps, higher education institutions can effectively contribute to the development of graduates who not only excel academically but also embody the principles of ethical leadership and social responsibility.